Принцип незалежності суддів як гарантія протидії порушенням прав людини в Україні - Кваша, О.О. (Часопис Київського університету права, 2009)
В статье анализируются проблемы независимости суда, как гаранта зашиты прав человека в Украине. Независимость судей как признак правового государства, в котором любой человек имеет право на судебную защиту своих прав и свобод, защищается уголовным законом Украины взаимосвязанной группой норм, предусмотренных статьями 376-379 КК Украины. In the article there are analyzed the issues of the court's independence that grants human's rights protection in Ukraine. Judge's independence as a feature of a legal state, where any person has a right to court trial and protection of his right and freedoms, is being protected by the inter-related group of norms, previewed by the articles 367-379 of the Criminal Code of Ukraine.